The specialized TV editorial market in Brazil : the Specialized a study on fan culture in Intervalo Magazine - Magnolo, Talita (2024)
This article analyses all 52 editions of the section "Entreviste seu Ídolo" from Intervalo magazine; based on the survey and analysis of issues published between 1968 and 1969, we discuss questions related to the fans profile chosen to participate in the section, the segment of activity of the idols and the context of the questions answered by the interviewees. In Brazil, despite being a minority, fan culture studies in communication are expanding and covering different areas such as identities, politics, and consumption. In this context, the article starts from a sample that has still not been explored in fan culture studies in the country. The magazine was a project of Editora Abril, published between the years 1963 and 1972; in turn, upon observing this strategic movement of the broadcasters and the consequent interest of its readers, it created several sections that established dialogues and built different relationships with its audience (Magnolo, 2023).